2014
DOI: 10.1002/ejoc.201402985
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Chiral Ferrocenophanes and Their Application to Asymmetric Catalysis

Abstract: N‐Substituted 2‐aza‐[3]‐ferrocenophanes were easily synthesized from 1,1′‐ferrocenedicarbaldehyde and aliphatic amines in high yields. One of the ferrocenophanes served as a ligand for the copper‐catalyzed oxidative coupling of 2‐naphthol derivatives to give the products in good yields with up to 92 % ee, and it also efficiently catalyzed the asymmetric Michael addition reaction as an organocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Selectfluor could oxidize Ag( i ) to Ag( iii ), which may undergo single electron transfer (SET) to give NO 2 radicals. 16,17 The NO 2 radical could dimerize to form the NO + NO 3 − ion pair, 18 which could oxidize the Pd( ii ) species A to give the Pd( iv ) species B . The nitrosyl-organopalladium( iv ) complex B could deliver 2a directly via reductive elimination (the nitrooxylation reaction gave 34% yield of the desired product under a N 2 atmosphere, see the ESI†) or react with O 2 to afford the O-bound nitrate complex C .…”
Section: Resultsmentioning
confidence: 99%
“…Selectfluor could oxidize Ag( i ) to Ag( iii ), which may undergo single electron transfer (SET) to give NO 2 radicals. 16,17 The NO 2 radical could dimerize to form the NO + NO 3 − ion pair, 18 which could oxidize the Pd( ii ) species A to give the Pd( iv ) species B . The nitrosyl-organopalladium( iv ) complex B could deliver 2a directly via reductive elimination (the nitrooxylation reaction gave 34% yield of the desired product under a N 2 atmosphere, see the ESI†) or react with O 2 to afford the O-bound nitrate complex C .…”
Section: Resultsmentioning
confidence: 99%
“…Among the available methods for the synthesis of optically active BINOLs, one of the most explored is the oxidative dimerization of 2-naphthols mediated by complexes of Cu [39][40][41][42][43][44][45][46] Fe [47][48][49], V [50][51][52][53][54][55], Ru [56], and chiral ligands (very often amines), normally generated in situ. In this regard, excellent reviews discussing these methods have been reported by Brunel [57], Wang [58], Bryliakov et al [59], and Liao et al [60] (Schemes 1 and 2).…”
Section: Metal-mediated Oxidative Enantioselective Couplingmentioning
confidence: 99%
“…Efficient vanadium-catalyzed [21] protocols were reported by the Uang [22], Chen [23], Gong [24][25][26], and Sasai [27][28][29] groups, independently. Many research groups, including Nakajima, Kozlowski, and others, have successfully developed a series of copper-catalyzed coupling reactions of 2-naphthols [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Recently, a notable work by the Tu group [45] established a Cu/SPDO (spirocyclic pyrrolidine oxazoline) complex-catalyzed cross-coupling reaction to synthesize 3,3 -disubstituted BINOLs.…”
Section: Introductionmentioning
confidence: 99%